Obstructive Jaundice as an Initial Manifestation of Non-Hodgkin Lymphoma: Treatment Dilemma and High Mortality - Dhara Chaudhari; Sarah Khan; Atif Saleem; Tamarro Taylor; Chakradhar Reddy; Thomas Borthwick; Mark Young (Case Reports in Medicine)
Introduction. Non Hodgkin lymphoma (NHL) presenting with obstructive jaundice is a rare occurrence. Because of rarity of combination, it is seldom considered in differential diagnosis of patients presenting with obstructive jaundice. It is considered treatable due to the chemosensitive nature of the disease and the recent advances in chemotherapy. Case Series. We present a case series of 2 patients with NHL presenting with obstructive jaundice as an initial manifestation. Both patients presented with obstructive jaundice and were diagnosed by CT guided liver biopsy. One patient died of sepsis and multiorgan failure before initiating chemotherapy and the second patient did not choose to undergo chemotherapy. Conclusion. Biliary obstruction is a sign of poor prognosis. The diagnosis of NHL needs to be considered in patients presenting with biliary obstruction. It can be associated with high mortality and poses treatment dilemma.